The Potential of Arbitrating Healthcare Disputes (Medico Legal Update, 2020)
The speedy progress of trade in Global Health Services is limited by legal barrier. Advances in technology andcross-border movement of people and health services form legal ambiguities and uncertainties for businessesand consumers involved in transnational medical malpractice disputes. This requires for a uniform meansof redress which is more flexible and predictable as compared to litigation in a court room. Therefore, thevoluntary, flexible and legally binding nature of arbitration agreements across jurisdictions make this formof dispute resolution efficient and adaptive to changes in the health services industry. With careful making ofan approach that accounts for arbitration cost, reasonable recovery amount and complementary mechanismssuch as no-fault compensation, international arbitration of medical malpractice disputes will change thelegal risks borne by businesses and consumers more fairly and efficiently.This paper argue that most medical disputes are better resolved by alternative dispute resolution mechanismswhich will contribute in improving patient safety by encouraging candid and comprehensive reporting ofrisks. It also argues that medical disputes and patient safety needs to be viewed through a new lens, namelypatient autonomy. It discusses the scope of India flourishing in the field of Medical Tourism and also thechallenges faced by the foreign patients and the scope of Arbitration in amicably resolving the medicaldisputes in a cost effective and in a swift manner.